Two robust Zn(ii)-organic frameworks as dual-functional fluorescent probes for efficient sensing of enrofloxacin and MnO4− anions. Issue 1 (29th November 2021) - Su, Yu-Qiao; Wang, Ruo-Tong; Blatova, Olga A.; Shi, Yong-Sheng; Cui, Guang-Hua
Abstract : Two robust Zn-MOFs were employed as visual and ultra-sensitive indicators toward enrofloxacin (ENR) and MnO4 − anions in aqueous phase. Abstract : Selective detection of antibiotics and MnO4 − is crucial for human health improvement and protecting the environment. Two stable Zn(ii )-based metal–organic frameworks (MOFs) {[Zn6 (L1)2 (NDC)5 ( μ 2 -OH)2 ]·0.5H2 O} n (1 ), and {[Zn(L2)(NDC)]·2H2 O}n (2 ) (H2 NDC = 1, 4-naphthalenedicarboxylic acid, L1 = 1, 5-bis(1-(pyridine-4-ylmethyl)-1 H -benzo[ d ]imidazol-2-yl)pentane, L2 = 1, 6-bis(1-(pyridine-4-ylmethyl)-1 H -benzo[ d ]imidazol-2-yl)hexane) were successfully synthesized by adopting the mixed ligands approach. 1 is a rare 3D 3, 5, 6T23 framework based polynuclear complex group. 2 possesses a 2D sql layer. The two MOFs exhibit excellent chemical and thermal stability. The title compounds are promising dual-functional fluorescent sensors for detecting enrofloxacin/MnO4 − anions with high selectivity and sensitivity ( K sv values toward enrofloxacin: 4.29 × 10 6 L mol −1 for 1 and 4.59 × 10 6 L mol −1 for 2 and toward MnO4 − : 1.05 × 10 4 for 1, 5.48 × 10 3 L mol −1 for 2, respectively), which are the first observations of fluorescent MOFs for the sensing of enrofloxacin and MnO4 − anions.